Enhanced light emission from Ge by GeO2 micro hemispheres. (August 2015) - Chen, Yen-Yu; Yen, C.-C.; Chang, T.-Y.; Liu, C.W.
Abstract: The integrated photoluminescence intensity of Ge with GeO2 micro hemispheres increases by a factor of more than 10 as compared to bare Ge. Decreasing the surface reflectance, the total internal reflection, and the surface recombination velocity by the formation of the micro hemispheres is responsible for the enhancement. The decrease of the surface recombination velocity and the total internal reflection to increase the light extraction by micro hemispheres also enhance the electroluminescence of Ge metal–insulator–semiconductor light emitting diodes.